Grounding the European public sphere: looking beyond the mass media to digitally mediated issue publics - Bennett, Lance (2012)
Abstract: The gold standard for discussing public spheres has long been established around mass media, with the prestige print press given a privileged place. Yet when it comes to a European public sphere, the mass media are also problematic, or at least incomplete, in several ways: relatively few EU-wide issues are replicated in the national media of EU countries, the discourses on those issues are dominated primarily by elites (with relatively few civil society voices included in the news), and public attention is seldom paid to EU issues beyond a select few (money, agriculture, political integration, scandals), creating a distant ‘gallery public.’ At the same time, many important political issues such as trade and economic justice, development policy, environment and climate change policy, human rights, and military interventions, among others, are being addressed more actively by networks of civil society actors both within and across EU national borders. These networks utilize the Inter